ChemInform Abstract: 2‐(Quinolin‐4‐ylthio)‐1, 3, 4‐oxadiazole Derivatives: Design, Synthesis, Antibacterial and Antifungal Studies. Issue 7 (18th February 2014) - Modh, Rahul P.; Shah, Dhruvin; Chikhalia, Kishor H.
Abstract The product (IIIa), (IIIb), (IIId), and (IIIf) show moderate activity against bacteria (E.